Financing and its influence on sales revenue: leche Gloria S.A. Case 1998-2018 - Vidaurre Díaz, Ceveriano Gregorio (2020)
Objective: To analyze the level of influence of financing in the sales revenue growth in Leche Gloria S.A (the former Gloria S.A.). company during the period 1998-2018. Method: The research approach is quantitative, the type research is basic with a descriptive, correlate - explanatory level in a non-experimental, longitudinal design, it means, perform the investigation with documentary information reported to the Superintendence of the Securities Market (SMV). Results: the equity increased in a rate of 6.72% annual average (56.36 million average per year), the financial debt increased in a rate of 5.87% annual average (29.75 million average per year) and the sales revenue increased 9.09% annual average (144.4 million average per year). Conclusions: It is confirmed that financing with financial debt and with equity influenced positive and significantly the sales revenue in Leche Gloria S.A. company during the period 1998-2018, has been shown in a individual way through the statistic t of Student , tc-Pat=17,20 and tc-DF=2,64 greater than tt =2,10 and the model with the F statistic , Fc =440,00 greater than Ft=3,55.